Effectiveness of Village Information Systems as Learning Media (in Kawengan Village) - Isnaini, Novia; Roemintoyo, Roemintoyo; Sukmawati, Fatma (Universitas Sebelas Maret, 2023)
Education is the key to developing human potential. In this digital era, the use of Village Information Systems has become one of the tools for expand-ing access and disseminating information to the community. In addition, the Village Information System opens up space as a learning medium in the world of education. This provides opportunities for people who previously had difficulty accessing formal education. The purpose of this study is to evaluate the effectiveness of the Village Information System as a learning media in Kawengan Village. The method used is a qualitative method with a case study approach. The determination of informants was carried out by means of interviews and document analysis to obtain data. The results of this study indicate that the Village Information System is very effective as a learning media in one of the villages in East Java. This is seen based on the focus of the research, which includes ease of access and relevant learning content, both for formal and non-formal education. The implication of this research is to develop human resources and the level of education in rural areas.